Biomimetic recyclable microgels for on-demand generation of hydrogen peroxide and antipathogenic application. (1st January 2019) - Meng, Hao; Forooshani, Pegah Kord; Joshi, Pratik U.; Osborne, Julie; Mi, Xue; Meingast, Christa; Pinnaratip, Rattapol; Kelley, Jonathan; Narkar, Ameya; He, Weilue; Frost, Megan C.; Heldt, Caryn L.; et al.
Graphical abstract: Abstract: Microgels that can generate antipathogenic levels of hydrogen peroxide (H2 O2 ) through simple rehydration in solutions with physiological pH are described herein. H2 O2 is a widely used disinfectant but the oxidant is hazardous to store and transport. Catechol, an adhesive moiety found in mussel adhesive proteins, was incorporated into microgels, which generated 1–5 mM of H2 O2 for up to four days as catechol autoxidized. The sustained release of low concentrations of H2 O2 was antimicrobial against both gram-positive ( Staphylococcus epidermidis ) and gram-negative ( Escherichia coli ) bacteria and antiviral against both non-enveloped porcine parvovirus (PPV) and enveloped bovine viral diarrhea virus (BVDV). The amount of released H2 O2 is several orders of magnitude lower than H2 O2 concentration previously reported for antipathogenic activity. Most notably, these microgels reduced the infectivity of the more biocide resistant non-envelope virus by 3 log reduction value (99.9% reduction in infectivity). By controlling the oxidation state of catechol, microgels can be repeatedly activated and deactivated for H2 O2 generation. These microgels do not contain a reservoir for storing the reactive H2 O2 and can potentially function as a lightweight and portable dried powder source for the disinfectant for a wide range of applications. Statement of Significance: Researchers have designed bioadhesives and coatings using the adhesive moiety catechol to mimic the strong adhesion capability of mussel adhesive proteins. During catechol autoxidation, hydrogen peroxide (H2 O2 ) is generated as a byproduct. Here, catechol was incorporated into microgels, which can generate millimolar levels of H2 O2 by simply hydrating the microgels in a solution with physiological pH. The sustained release of H2 O2 was both antimicrobial and antiviral, inactivating even the more biocide resistant non-enveloped virus. These microgels can be repeatedly activated and deactivated for H2 O2 generation by incubating them in solutions with different pH. This simplicity and recyclability will enable this biomaterial to function as a lightweight and portable source for the disinfectant for a wide range of applications.